2010
DOI: 10.1017/s1751731109991704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of housing conditions on activity and lying behaviour of horses

Abstract: Housing conditions for horses impose various levels of confinement, which may compromise welfare. Lying behaviour and activity can be used as welfare indicators for domestic animals and rebound behaviour suggests a build-up of motivation resulting from deprivation. The objective of this study was to determine if activity and lying behaviour of horses are affected by housing conditions and to investigate the occurrence of rebound behaviour after release from confinement. Eight horses were subjected, in pairs, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 13 publications
5
39
0
Order By: Relevance
“…Lying bouts occurred during the night, which is consistent with the existing literature (Chaplin and Gretgrix, 2010). These findings are further supported by earlier work done by Dallaire and Ruckebusch (1974) who reported that older horses were less likely to lie down during the day when compared with younger animals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lying bouts occurred during the night, which is consistent with the existing literature (Chaplin and Gretgrix, 2010). These findings are further supported by earlier work done by Dallaire and Ruckebusch (1974) who reported that older horses were less likely to lie down during the day when compared with younger animals.…”
Section: Discussionsupporting
confidence: 91%
“…which is similar to the maximum bout length (32.5 min) documented by Chaplin and Gretgrix (2010) for horses that were partially stabled, however the standard deviation indicates that there was considerable variation among bouts. Bout duration ranged from as little as 4 min to as long as over an hour, and little is known about what factors affect lying bout duration.…”
Section: Discussionsupporting
confidence: 75%
“…In a study by Kiley-Worthington (1989, cited in Zeitler-Feicht 2001 a lying period of 10 % of the time budget of horses could be ascertained in loose-housing on straw with hay being available ad libitum, while in the case of strawless box stall housing with rationed hay 16 % of the time budget was given over to lying. In contrast, a study of Chaplin and Gretgrix (2010) with eight horses showed no significant affect of the housing conditions (paddock, fully stabled, partly stabled or yard) on the total time spent lying.…”
Section: Introductionmentioning
confidence: 71%
“…According to Crowell-Davis (1994) this is responsible for the psychological well-being of horses. Furthermore, lying behaviour can be used as welfare indicator for domestic animals (Chaplin and Gretgrix 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Every additional motion caused a reduction of the stress load (Hoffmann et al, 2009). Chaplin and Gretgrix (2010) also showed that housing conditions have a strong influence on the activity behavior of horses. In their investigation, horses were significantly more active when they were kept in a large paddock day and night than when they were stabled in a loose box.…”
Section: Introductionmentioning
confidence: 94%